2022
DOI: 10.1039/d2ta00959e
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient organic solar cells with superior deformability enabled by diluting the small molecule acceptor content

Abstract: Developing efficient organic solar cells (OSCs) with strong mechanical deformability is urgent to be addressed to promise their operational reliability in wearable electronics. However, it is challenging to achieve mechanical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The peak location evolution of both two films can be divided into three stages. [ 36 ] A test interval (0.5 s) is adopted here to investigate the film‐drying kinetics of the active layer. If the peak location change of each interval is larger than 1 nm and this tendency does not change anymore, we define that a stage is finished, and the film drying process comes into the following stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak location evolution of both two films can be divided into three stages. [ 36 ] A test interval (0.5 s) is adopted here to investigate the film‐drying kinetics of the active layer. If the peak location change of each interval is larger than 1 nm and this tendency does not change anymore, we define that a stage is finished, and the film drying process comes into the following stage.…”
Section: Resultsmentioning
confidence: 99%
“…The peak location evolution of both two films can be divided into three stages. [36] A test interval (0.5 s) is adopted here to investigate the film-drying kinetics of the active layer. If the a) The device areas are 0.0256 cm 2 ; b) The device areas are 1 cm 2 .…”
Section: Formation Kinetics Of Slot-die-coated Filmsmentioning
confidence: 99%
“…Many strategies have been used to improve their mechanical properties, including physically mixed insulating polymers (PS, PDMS, SEBS, etc. ), covalently linked insulating polymer chains into the backbones or side chains, ternary OSCs by using the third conjugated components, and adjusting the amorphous/crystalline nature. These methods can indeed help to improve the COS, but there are still some issues. For example, the addition of insulating polymers will dilute the conjugated components, and the enhancement of the amorphous region will lower charge carrier mobilities and PCEs in OSCs. , It will be an important task to develop conjugated polymers with excellent mechanical properties and meanwhile provide high performance in OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, crystallinity is an important parameter to be considered for morphology optimization . Using a highly crystalline small molecule donor as a third component improves the overall crystallinity of the ternary blend and does not produce excessive aggregation, thus mixing the polymer donor with the small molecule donor provides a way to obtain optimal morphology. , For example, Zhang et al added a small molecule (SM) donor BPR-SCl with deep highest occupied molecular orbital (HOMO) energy level and strong crystallinity to the PM6:BTP-eC9 system to enhance the crystallinity of the active layer, which slightly reduced the phase separation to promote exciton separation, enhance the hole mobility, and yielding a high efficiency of 18.02%. Zhao et al reported a TOSC based on PM6:TTBT-R:Y6, designed asymmetric molecule TTBT-R with high crystallinity and good compatibility with PM6.…”
Section: Introductionmentioning
confidence: 99%